2020
DOI: 10.1039/d0cp02869j
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, optical and thermoelectric properties of boron-doped nitrogenated holey graphene

Abstract: We employ first principles calculations to investigate the electronic, optical, and thermoelectric properties of ten boron-doped nitrogenated holey graphene (NHG) monolayers. We find that most of the proposed structures remain...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…The bond lengths within these rings are Å and Å for one ring, and Å and Å for the other ring, as depicted in Figure . These bond length values are consistent with those observed in similar 2D carbon allotropes. , Notably, the formation energy of S-GY is −8.57 eV/atom, which closely resembles that of graphene (−8.8 eV/atom). ,, …”
Section: Resultssupporting
confidence: 86%
“…The bond lengths within these rings are Å and Å for one ring, and Å and Å for the other ring, as depicted in Figure . These bond length values are consistent with those observed in similar 2D carbon allotropes. , Notably, the formation energy of S-GY is −8.57 eV/atom, which closely resembles that of graphene (−8.8 eV/atom). ,, …”
Section: Resultssupporting
confidence: 86%
“…9), and a higher ZT peak along the ac -direction. Such an an-isotropy has been recently reported in boron-doped nitrogenated holey graphene, 76 and orthorhombic MLs of GeSe, SnS, and SnSe. 77 It is interesting to note that alloying has enhanced the ZT max significantly (by a factor of about 3) making it greater than unity, and it is on a level with the ZT max in buckled antimonene.…”
Section: Resultssupporting
confidence: 63%
“…Interestingly, it has been observed that doping with the B or N atom increases the band gap, thus leading to a large Seebeck coefficient and high thermoelectric performance of BN-doped γ-graphynes compared to pristine γ-graphyne. Incorporating B and N atoms in other systems such as holey graphene, graphene oxide, and so forth significantly enhances the thermoelectric performance, , which is another reason for choosing B and N atoms as dopants in our present study. For any thermoelectric device, p-type and n-type materials need to be arranged in a tandem device to increase its thermal voltage output.…”
Section: Introductionmentioning
confidence: 95%